1982
DOI: 10.1111/j.1469-8137.1982.tb03403.x
|View full text |Cite
|
Sign up to set email alerts
|

GENECOLOGICAL STUDIES OF URTICA DIOICA L.

Abstract: SUMMARYUrtica dioica L. shows considerable variation in several characters, including stinging hair density. Members of a particular population found at Wicken Fen are remarkable in that they bear almost no stinging hairs, are tall, unbranched, narrow-leaved, and late-flowering. Experimental cultivation of samples from Wicken and a number of other populations showed that:(i) Plants retain many of their distinctive features in cultivation.(ii) Some of the variation is apparently heritable.(iii) There are signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…Stocks of dioica were collected in Montreal (Canada) and Montgomery Co., MD (U.S.A.), and stocks of gracilis were collected in Skagit Co., Washington (U.S.A.). No monoecious individuals were observed in either source population of dioica, although they have been documented in other natural populations Pollard & Briggs 1982) and might be found in these two populations on closer examination. Progeny from all crosses were grown to flowering in University of Connecticut greenhouses.…”
Section: Methodsmentioning
confidence: 52%
“…Stocks of dioica were collected in Montreal (Canada) and Montgomery Co., MD (U.S.A.), and stocks of gracilis were collected in Skagit Co., Washington (U.S.A.). No monoecious individuals were observed in either source population of dioica, although they have been documented in other natural populations Pollard & Briggs 1982) and might be found in these two populations on closer examination. Progeny from all crosses were grown to flowering in University of Connecticut greenhouses.…”
Section: Methodsmentioning
confidence: 52%
“…However, available soil moisture content is considered as a key variable for triggering phenological events in plants (Singh and Singh 1992). Phenological patterns of different plant species occurring in the diverse habitats is also determined by their genetic character (Pollard and Briggs 1982). Subalpine habitats are characterized by short growth season, heavy snowfall, low and fluctuating diurnal temperature, occasional hailstorms and physiologically unavailable soil moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that U. dioica from high altitudes have more medicinal value that might be due to more stinging hairs and the amounts and variability of antioxidants and phenolic contents of U. dioica according to previous researches (Pollard and Briggs, 1982) whereas with our limited samples we could show that Erzurum accessions from the highest altitute (1890 m) has the highest total antioxidant and phenolic contents (Table 5) of leaf infusions when compared with the other city accessions (Figure 3). It is only for the leaf infusions not for methanol extracts and infusions of stems and roots of Erzurum accessions (data not shown) come first that is to be further confirmed with more samples with more controlled growth parameters.…”
Section: Resultsmentioning
confidence: 51%
“…Urtica dioica is one of the 2000 taxa of plants evaluated for medicinal and aromatic purposes and still one of the 500-1000 taxa of plants used as traditional medical use.The use of Urtica dioica as a drug prepared from medicinal plants in Turkish traditional medicine dates back centuries ago and it has a big part in ethnobotanical usage as food in Turkey (Davis, 1965(Davis, -1985 U. dioica, is a herbaceous perennial flowering plant species, highly variable in size, branching, leaf and inflorescence form and degree of hairiness. Cultivation experiments carried out by Pollard & Briggs (1982) with individuals from nine populations covering a range of habitat provide evidence that phenotypic plasticity is important in U. dioica; for example, fewer hairs were produced on plant grown in the shade than on those in full sun. These experiments also support the conclusion that much of the variation (including the polymorphism in stinging-hair density) is genetically based and heritable (Pollard and Briggs 1982;Bharmauria, et al, 2009;Taylor, 2009).…”
Section: Introductıonmentioning
confidence: 99%
See 1 more Smart Citation